A REVIEW ON REHEATED COOKING OIL AS AN ASPECT OF SANSKAR VIRUDDHA (AYUSHDHARA, 2016)
Ayurveda is a science of life. Ayurveda focuses more to remain healthy and prevent diseases. To become healthy, diet plays a very important role. All the Ayurvedic classics have paid special attention on the concept of wholesome and unwholesome diet. The food, which maintains the balanced Dhatus in normalcy and restores the equilibrium, should be taken as wholesome. Unwholesome diet i.e. Viruddha Ahara is a special concept described in Ayurvedic literature. Different types of Viruddha’s have been mentioned according to place, time, digestion power, dosage, habit, doshas, mode of preparation and so on. Samskar Viruddha is that where food is converted into harmful substances during the course of preparation emerging ill effects on health. In current scenario examples of Samskar Viruddha Ahara are being changed due to changing life style, urbanization and fascination of western culture. Though there is noticeable change in food habits and preparatory methods between early time and in present era, the principle (Ayurvedic siddhant) behind this remained the same. Today’s lifestyle is very fast, full of hurry. As a result consumption of ready-made food is in much demand. And if it is deep-fried then its demand becomes even higher. Edible vegetable oil is the major ingredient in these fried food products. Reusing this deep fried oil repeatedly for frying purposes leads to many health hazards. The efforts have been made here to elaborate health effects of reusing cooking oil for frying process as an account of Samskar Viruddha.